Management of Skin Toxicities of Anti-EGFR Agents in Patients with Pancreatic Cancer and Other GI Tumors by Using Electronic Communication: Effective and Convenient - Saif, Muhammad Wasif; Kaley, Kristin; Lamb, Lynne; Pecerillo, Jennifer; Hotchkiss, Susan; Steven, Lisa; Brennan, Marianne; Penney, Robin; Gillespie, Carolyn; Shaib, Walid (JOP. Journal of the Pancreas, 2010)
Erlotinib has been FDA approved to be used in combination with gemcitabine as the first line treatment in advanced pancreatic cancer patients. Skin rash has been documented as one of the commonest adverse reactions in patients receiving erlotinib and other EGFR inhibitors. Draw back to this reaction leads to: 1) drug discontinuation or dose reduction; 2) impairs quality of life; and 3) Puts patients at risk of superinfection. Monitoring patients closely and initiating immediate skin care is recommended. However, patients forget how the rash started and when. No standard treatments exist secondary to the diversity of symptoms, variability and intermittent occurrence in relation to the cancer therapy. In addition, there is slow improvement with medical treatment. Also, patients need to make extra visits to doctor’s office for skin management when in needed in addition to chemotherapy appointments. Late presentation for medical attention leading to complications, such as sepsis. We here experience a novel way of assessing and managing the skin rash using the electronic media. We suggest that electronic communication is of crucial importance to detect early, diagnose and treat anti-EGFR related skin rash in order to continue the benefit of anti-EGFR. Image: Risk assessment and management algorithm.